Implicaciones sociales y económicas del entorno global:notas para la discusión - María Estela Orozco Hernández (Ciencia Ergo Sum)
The Revista or Memorias de la Sociedad Científica Antonio Alzate was a monthly publication, edited by the society of the same name founded on October 4th, 1884, in memory of the great Mexican intellectual Antonio Alzate. This publication became one of the most important scientific Mexican journals of its time, due to the high academic quality of its Mexican and foreign contributors. In this work we analyze and elaborate a database of the articles published in Memorias through which we can observe the transition from classical to modern physics in Mexico